2008
DOI: 10.1182/blood-2007-04-087882
|View full text |Cite
|
Sign up to set email alerts
|

The opposite effects of IL-15 and IL-21 on CLL B cells correlate with differential activation of the JAK/STAT and ERK1/2 pathways

Abstract: The clonal expansion of chronic lymphocytic leukemia (CLL) cells requires the interaction with the microenvironment and is under the control of several cytokines. Here, we investigated the effect of IL-15 and IL-21, which are closely related to IL-2 and share the usage of the common ␥ chain and of its JAK3-associated pathway. We found remarkable differences in the signal transduction pathways activated by these cytokines, which determined different responses in CLL cells. IL-15 caused cell proliferation and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
106
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(114 citation statements)
references
References 68 publications
7
106
1
Order By: Relevance
“…IL-15Ra is poorly expressed in the absence of stimulation in B cells from hematological diseases and is upregulated by in vitro stimulation with CD40L (11,35). In random CLL samples, fluorescent rhIL-15 binds B leukemic cells, and this is decreased significantly in the presence of a blocking IL-15Ra mAb (Fig.…”
Section: B Leukemic Cells As Accessory Cells For Rhil-15-induced Nk Cmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-15Ra is poorly expressed in the absence of stimulation in B cells from hematological diseases and is upregulated by in vitro stimulation with CD40L (11,35). In random CLL samples, fluorescent rhIL-15 binds B leukemic cells, and this is decreased significantly in the presence of a blocking IL-15Ra mAb (Fig.…”
Section: B Leukemic Cells As Accessory Cells For Rhil-15-induced Nk Cmentioning
confidence: 99%
“…These included hematological pathologies, such as chronic lymphocytic leukemia (CLL), in which recombinant human IL-15 (rhIL-15) sustains the survival of leukemic cells in vitro (11).…”
mentioning
confidence: 99%
“…32 Our detailed analysis of CD40L-and IL-15-driven signals provides clues to their respective roles in normal B cell behavior. Intriguingly, our study provides evidence that the observed synergy between IL-15 and CD40L in normal and FL B cells is based on a different mechanism from that reported in CLL B cells, which involved an 19 We demonstrated for the first time that CD40L drives an increase in the expression of total STAT5 in tonsil B cells. This unexpected result corroborates with the identification of a small population of activated tonsil GC B cells displaying an increased expression of total STAT5 and committed to memory cell fate.…”
Section: Discussionmentioning
confidence: 63%
“…The increased sensitivity of CD40-activated B-CLL cells to mitogenic effects of IL-15 was previously associated with an increased expression of IL-15Ra and IL-2Rb. 19 However, the level of IL-15Ra was not affected by CD40 triggering in normal B cells at both mRNA and protein levels. In addition, the faint upregulation of IL-2Rb and IL-2Rg was associated with a very limited increase in their capacity to bind exogenous IL-15 (Supplementary Figure S4).…”
Section: Il-15 and Cd40l Synergy In B Cells G Epron Et Almentioning
confidence: 99%
See 1 more Smart Citation